Role of color doppler in the diagnosis of intra uterine growth restriction (IUGR) - Singh, Shivani; Verma, Urvashi; Shrivastava, Kumkum; Khanduri, Sachin; Goel, Nancy; Zahra, Fatima; Shirivastava, K. L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The purpose of our study was to evaluate the diagnostic efficacy of the pulsatility index (PI) and resistive index (RI) in uterine artery, umbilical artery and middle cerebral artery in the diagnosis of IUGR and prediction of adverse perinatal outcome. Methods: A total of 100 clinically suspected IUGR cases were enrolled in the study. A detailed history and examination was done, color doppler carried out serially every three weeks starting from 30 weeks till delivery, subsequently confirmation of fetal growth restriction (FGR) was done by assessing the newborn parameters for growth restriction. Results: Doppler measurement for uterine artery showed higher efficacy as compared to umbilical artery and middle cerebral artery findings. The uterine artery RI was found to be 84.6% sensitive and 82.9% specific even at 30 weeks. Uterine artery PI too showed a good diagnostic efficacy with an accuracy of 79%, a sensitivity of 76.9%, a specificity of 82.9%.Both PI and RI for uterine artery showed a relatively higher specificity. Conclusion: Here we concluded that once IUGR is suspected, Doppler velocimetry may be useful as a part of evaluation and uterine artery analysis identifies a subgroup with an increased risk for developing IUGR.